Necessity or Unnecessary of writing Gemination in the Persian language - آسیه ذبیح نیا عمران (مطالعات زبانی و بلاغی)
The plenty and variety of the Geminated Words indicates that certainly Gemination appears in the speech and speakers of the Persian language know this. The obvious reason is that Persian speakers whether young or old produce Gemination systematically and they have no problem in producing, it but there is hesitation if the sing of Gemination in writing is a cause of reading the stressed words fluently and correctly. The similar voices in some words are pronounced Gemination and in some without geminating, however their voice structure are the same. Generally geminating has an important part in the Persian language because it is the result of a method of language phonology that according to a unexceptionable method and unwontedly is used by the speakers. This article is written according to the library's method research and presented both descriptively & analytically.